2007
DOI: 10.1021/cg070218y
|View full text |Cite
|
Sign up to set email alerts
|

Making Co-CrystalsThe Utility of Ternary Phase Diagrams

Abstract: We describe the use of ternary, isothermal phase diagrams of co-crystal-forming systems as a basis for understanding current crystallization methodologies and for experimental design in the preparation of co-crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
253
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(258 citation statements)
references
References 19 publications
3
253
0
Order By: Relevance
“…This was not entirely unexpected, as the isolation of pure cocrystal phases can require detailed understanding of the ternary phase diagrams for the acid, nicotinamide and the solvent; especially when narrow regions of stability exist for the pure cocrystal phase. 26 This work is currently underway and will be reported in a forthcoming publication. The ratio given is the acid : nicotinamide molar ratio in the solid mixture.…”
Section: Resultsmentioning
confidence: 99%
“…This was not entirely unexpected, as the isolation of pure cocrystal phases can require detailed understanding of the ternary phase diagrams for the acid, nicotinamide and the solvent; especially when narrow regions of stability exist for the pure cocrystal phase. 26 This work is currently underway and will be reported in a forthcoming publication. The ratio given is the acid : nicotinamide molar ratio in the solid mixture.…”
Section: Resultsmentioning
confidence: 99%
“…A three-component phase diagram of the benzamide:dibenzyl sulfoxide cocrystal in water at 37 °C was constructed, based on methods previously described (Ainouz et al, 2009;Chiarella et al, 2007;Nehm et al, 2006), and is shown in Figure 9. The cocrystal solution equilibrium is described by…”
Section: Ternary Phase Diagrammentioning
confidence: 99%
“…The liquid additive is, however, present in sufficiently small amounts for the system to thermodynamically behave as if it were solvent-free. 26 Consequently, LAG reactions are not affected by limitations of solubility that plague solution-phase reactivity 27 and mechanochemical screening can rapidly provide cocrystals based on starting materials that are too soluble for efficient cocrystallization from solution, or cocrystals of composition that is difficult to obtain by solution growth. The ability to efficiently conduct reactions in stoichiometric compositions that are not effective in solution has also been observed in organic mechanosynthesis.…”
Section: Mechanosynthesis In Organic Synthesis and Cocrystallizationmentioning
confidence: 99%